Influence of Growth Parameters on the Formation of Hydroxyapatite (HAp) Nanostructures and Their Cell Viability Studies - Manoj, M.; Subbiah, R.; Mangalaraj, D.; Ponpandian, N.; Viswanathan, C.; Park, K. (SAGE Publications Ltd, 2015)
Morphology controlled hydroxyapatite (HAp) nanostructures play a vital role in biomedical engineering, tissue regenerative medicine, biosensors, chemotherapeutic applications, environmental remediation, etc. The present work investigates the influence of temperature, pH and time on the growth of HAp nanostructures using a simple, cost effective and surfactant free chemical approach. The obtained HAp nanostructures were systematically investigated by analytical techniques such as XRD, FESEM, EDX, FTIR and Raman spectroscopy. The XRD analysis showed that the hexagonal structure of the hydroxyapatite and average crystallite size was estimated from this analysis. The electron microscopic analysis confirmed the different morphologies obtained by varying the synthesis parameters such as temperature, pH and time. The elemental composition was determined through EDS analysis. FTIR and Raman spectroscopic analysis confirmed the presence of functional groups and the purity and crystallinity of the samples. The biocompatibility and adhesion nature of samples was examined with mouse preosteoblast cells. The obtained results demonstrated good biocompatibility and excellent focal adhesion. ？ 2015, ？ 2015 The Author(s). Licensee InTech.